Design of a collaborative system for real time haptic feedback in distributed virtual environments over IP networks - Yap, Kian Meng * (2011)
This paper presents an investigation into system architectures for real time haptic feedback in distributed virtual environments over IP switched network. Network impairments such as time delay, jitter and packet loss have a different impact on remote haptic collaborations than the traditional master-slave tele-operation. A hybrid architecture has been proposed and developed to address the challenges in the new use scenario. Experiments have been conducted to show the performance of this architecture in comparison with the currently available time delay compensation algorithms, i.e. dead reckoning. A set of network Quality of Service (QoS) parameters for these types of haptic collaborative systems is obtained. Findings of the study are presented in the paper with recommendations for developing systems that support haptic collaboration.